2004
DOI: 10.1177/1082013204046095
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phenolic Compounds and Colour Parameters of Red Wine Aged with Oak Chips and in Oak Barrels

Abstract: Changes in phenolic compounds and colour related parameters of a red wine, Cigales Appellation of Origin, were monitored during its ageing in oak barrels and with added oak chips. Results were statistically analysed by multifactor analysis of variance and discriminant analysis. The wine aged in contact with oak chips underwent a quicker ageing, their loss of anthocyanins was also faster and suffered a higher number of polymerisations than the wine aged in barrels. Red wine colour changed during ageing due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 17 publications
6
29
2
1
Order By: Relevance
“…The highest increase was observed in AC sample (Figure 2a). These results are in agreement with Del Alamo et al (2004), who reported a progressive decrease of TP in wines during the first months of aging in contact with chips while after the third month an increasing trend was observed. Moreover, Gordillo et al (2013) reported an increase in TP as a result of wood chip addition during fermentation after two months of contact with the wine, which is also in agreement with the results presented above.…”
Section: Phenolic Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…The highest increase was observed in AC sample (Figure 2a). These results are in agreement with Del Alamo et al (2004), who reported a progressive decrease of TP in wines during the first months of aging in contact with chips while after the third month an increasing trend was observed. Moreover, Gordillo et al (2013) reported an increase in TP as a result of wood chip addition during fermentation after two months of contact with the wine, which is also in agreement with the results presented above.…”
Section: Phenolic Contentsupporting
confidence: 93%
“…The different wood types did not result in significant differences among the samples (with the exception of A sample during the first month). These results confirm previous studies (Del Alamo Sanza et al, 2004 ;Gambuti et al, 2010) showing a positive effect of wood aging on red wine color stabilization. However, when chips were added during fermentation, a different pattern was observed.…”
Section: Color Parameterssupporting
confidence: 92%
“…Colour intensity and hue, determined by absorbance measurements of diluted or undiluted samples at the wavelengths of 420 (yellow), 520 (red) and 620 nm (violet), were also evaluated employing one-centimetre polystyrene cuve es (28,29). The equations for the calculation of colour intensity (CI) and hue (h) were as follows:…”
Section: Colour Intensity and Huementioning
confidence: 99%
“…Different extraction methodologies, such as simultaneous distillationextraction (SDE), Soxhlet extraction , liquid-liquid extraction (Caldeira et al, 2004), solid-phase micro-extraction (SPME) (Jordão et al, 2006;Bozalongo et al, 2007) and accelerated solvent extraction (ASE) (Vichi et al, 2007), have been tested to meet sample preparation requirements. The phenolic compounds of red wine aged in contact to oak chips have also been identified (Del Alamo et al, 2004a, 2004bMatejícek et al, 2005;Del Alamo & Domínguez, 2006;Pérez-Magariño et al, 2009). To the best of our knowledge, the phenolic composition of oak or oak chips has not yet been studied from an oenological point of view, with the exception of several works describing oak and chestnut wood used in brandy ageing (Canas et al, 1999(Canas et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%